Gender equity considerations in food environments of low and middle income countries: A scoping review - Twyman, Jennifer; Elise, Talsma; Togka, Konstantina; Ferraboschi, Chiara; Brouwer, Inge D. (International Food Policy Research Institute, 2020)
This study presents the results of a scoping literature review of gender equity in food environments of low- and middle-income countries. We start by examining the concept of food environments; and find that dividing the concept into two parts, one related to the food supply chain, and the other related to consumer behavior is useful for categorizing literature. One key finding is that although we specifically concentrated our search on articles related to gender in the food environment, the articles found focus more on the food supply chain and/or consumer behavior rather than specifically on the food environment. Most of the articles related to the food supply chain are based on studies conducted in Africa while most of the consumer behavior articles are from studies done in Asia. While gender equity is a topic of interest and is often said to be a priority for international development, relatively few articles were found about how gender equity impacts and/or is impacted by food environments. Those that do exist suggest that a food systems approach to healthier diets consider gender roles and responsibilities (i.e. gender division of labor and time use concerns), gendered access to and control over resources, and gender in decision-making processes. Gender norms related to these issues can present barriers to achieving the desired outcomes of food system interventions; on the other hand, they may also offer opportunities or clues about how to better move forward to achieve both food and nutrition security, and gender equity and equality goals.